Justicia neolinearifolia N.H. Xia & Y.F. Deng, a new record for the flora of Vietnam - Hai, Do Van; Khoi, Nguyen Khac; Yunfei, Deng (Academia Journal of Biology, 2015)
Justicia neolinearifolia N. H. Xia & Y.F. Deng (Acanthaceae) found in Lai Chau province is reported here for the first time for the flora of Vietnam. J. neolinearifolia can be distinguished from J. procumbens L. and J. diffusa Willd. by having linear leaf blade and bracts. The specimens are deposited in the Herbarium of the Institute of Ecology and Biological Resources (HN) Ha Noi, Vietnam. A detailed description, illustration, important taxonomic notes, and key to the three already known species are provided.